Performance of Eggs White-Nest Swiftlet (Collocalia fuciphaga) on Artificial and Natural Hatching - Nurul Amin; Sudirman Baco; Herry Sonjaya; Wempie Pakiding (Hasanuddin Journal of Animal Science (HAJAS), 2021)
Abstract White-nest swiftlet (Collocalia fuciphaga) has a high export economic value. The nest is produced from the saliva of the swiftlet. Presently, its method of producing swiftlet chick is through the natural breeding process.  Until now, white-nest swiftlet has not been cultivated so that the method of procuring Swiftlet chicks is still using the parent. Therefore, to see the prospects for the cultivation of this bird, another way is needed to procure swiftlets by incubating the eggs using an incubator and looking at the physical characteristics of the eggs. This study aims to examine the performance of white-nest-swiftlet eggs in natural and artificial hatching in producing swiftlet chicks. The method was used the descriptive analysis method and t-test. The physical characteristics obtained were an average egg weight of 1.94±0.13 g, egg diameter 13.28±0.56 mm, egg length 21.01±0.78 mm, shell thickness 0.14±0.02 mm. Artificial hatching results obtained were 83%, hatchability 44%, and hatching weight 1.37±0.13 g. Age of embryonic death obtained early: 38.5%, middle: 9.8%, late: 21%. Natural hatching resulted in 100% fertility, 100% hatchability, hatching weight 1.42±0.11 g., and 0% mortality. Artificial hatching is an alternative for developing white nest-swiftlet. Keywords: Natural, artificial, fertility, hatchability, mortality